Lesson Plan - Melgoza-Mendoza, Dulce M; Rojas-Vite, Cristhian (Ciencia Huasteca Boletín Científico de la Escuela Superior de Huejutla, 2018)
An important instrument of the teacher is, without doubt, the lesson plan. Knowing how significant this entails this article has been made with the purpose of strengthening and facilitating the process of it. It is necessary to take into thought the following aspects as they are: the context of the group, the number of students that make it up, a period of time, hours of classes taught, characteristics of the group, types of learning and its external context. For this reason, it has made reference to some guidelines to reinvigorate the teaching instrument and thus be able to provide a significant teaching-learning.